1351 Osteopenia in High Risk Preterm Population in Manitoba: A Case-Control Study. (October 2012) - Soylu, H; Ali, E; Reed, M; Fast, S; Moisiuk, SE; Seshia, MM
Abstract : Background: Despite recent advances in care of VLBW infants, osteopenia of prematurity (OP) remains an important problem in most NICUs. Objective: To compare demographic, perinatal and postnatal characteristics of OP in VLBW babies admitted to our Level III NICU, to elucidate risk factors and association of biochemical bone markers with radiological changes and the clinical outcome. Design/methods: Infants born ≤29 weeks GA and admitted between October 2007 to January 2011. Only those infants with both chest X-rays and biochemical markers at or beyond 6 weeks post natal age were included. Infants were grouped as cases and controls based on serum Ca, P, ALP and X-ray findings and were stratified by GA: 24–25, 26–27 and 28–29 weeks. X-ray findings and biochemical results were considered in 2 week periods. Results: Of 176 potentially eligible infants 54 (GA 26.9±0.2 wks, BW 970±34 g) met the criteria for inclusion. 26% of the cases vs. 3% of the controls were from communities north of the 55° latitude (p<0.05). Serum Ca levels were within the normal range, but serum P levels were subnormal. The most significant biochemical discriminator between the two groups was the serum ALP level. Conclusions: Our results suggest that geographic factors may be a surrogate marker for maternal factors contributing to the etiology of OP. Future prospective studies may be helpful to define this. Biochemical markers, excepting ALP, are not predictive for OP diagnosis.